Conflicting senses of the natural physical environment (land) and technology in the Amazon: reviewing the stimulus to rubber plantations in 1900-1915 - Bentes, Rosineide da Silva (Seven Editora, 2023)
In the Amazon, in the promotion of rubber plantations, in the years 1900-1915, the territorial sense of land - soil to be deforested for monoculture - collided with the ecological rubber tree property in which land meant the elastic gum forest. This defined the size and contours of the property. The promoters of the plantations built the "civility" of these in contrast to the "incivility" of the ecological rubber tree property. The Brazilian policy for rubber promoted plantations, but this policy did not avenge them. And although several entrepreneurs have tuned in to it, the vast majority of seringalistas (the owners of rubber companies) opposed monoculture, claiming that it would destroy one of its main capitals: the rubber forest.DOI: https://doi.org/10.56238/devopinterscie-009